Heterogeneous Objects Modelling and Applications: Collection of Papers on Foundations and Practice - Pasko, Alexander; Adzhiev, Valery; Comninos, Peter (Lecture Notes in Computer Science, 2008)
Heterogeneous object modelling is a new and quickly developing research area. This book is one of the first attempts to systematically cover the most relevant themes and problems of this new and challenging subject area. It is a collection of invited papers and papers co-authored by the editors.